Cultura organizacional y satisfacción laboral en la facultad de Ingeniería Industrial en el marco de la acreditación universitaria - Tinoco Gómez, Oscar (2014)
The contemporary world requires consolidated organizations and institutions with the capacity to adequately fulfill its mission and vision, in which human resource plays a crucial role. Each organization has their uniqueness in organizational culture, it can be managed according to the strategic plan of the same. It is noteworthy that the organizational culture is not formed through speeches, but through strong actions. Similarly, the level of satisfaction of the people who work at the institution, public or private, is an aspect not missed in modern management, while its action depends on the achievement of organizational objectives. The study addressed the relationship between organizational culture and job satisfaction of teachers establishment of the Faculty of Mechanical Engineering of San Marcos, the same which looked upon the recognition of the state of research related to the problem of art, theoretical elaboration of each of the variables , arriving at their instruments measuring constructs. A direct relationship between the two variables was found.